Empowering Children With Autism To Success: Within Appropriate Ecosystem - Helmi Kassim; Siti Darzalina Mat Zoki; Noor Hassline Mohamed (2020)
Early detection of developmental delays in children coupled with appropriate intervention is crucial to help children develop to their fullest potential. Over the next few years, Ministry of Social and Family Development (MSF) will work with the Ministry of Health (MOH) to form a network of touch points across the health and preschool sectors. This would include doctors at the hospitals, polyclinics and family medicine practitioners in developmental screening, and pre-school teachers in early detection of children with developmental needs, so that they can be supported through timely intervention. Children with Autism Spectrum Disorder (ASD) have a unique profiling personality in terms of diverse intelligence, natural learning patterns and styles, the most effective natural learning method and the thinking mindset. The journey begins when a child has been diagnosed with Autism, be it verbal or non-verbal. As days passed, some parents may wonder what they could do for the sake of them and their child. This paper draws attention to the strategies of how we can empower the child with ASD to gain success in life within an appropriate ecosystem. The ecosystem supports children with disabilities (ASD) and their families, so as to improve their quality of life. Existing initiatives will be enhanced to provide more holistic help and a smoother transition for children with ASD at different stages of their lives.